Kuliah Kerja Nyata Tematik (KKNT) di Desa Tanjung Atap Kecamatan Tanjung Batu Kabupaten Ogan Ilir - Alviona; Audia Rosita; Ayu Laili Artanti; Kholifa khoirunnisa; Nadya dinda Dhea widianty; Rella Annisa Fitri; Nini Anggraini; Zaki Athallah; Ade Putra (CV. Doki Course and Training, 2024)
The university has Tri Dharma, one of the pillars of which is community service. One of the Community Service activities is KKN, and the author conducted Thematic KKN in Tanjung Atap Village in Tanjung Batu District, Ogan Ilir Regency, South Sumatra which focuses on community empowerment, students can explore local potential, educate the community, and design programs that are in accordance with the needs and characteristics of the village. KKNT activities are carried out using the Participatory Action Research (PAR) method which generally has a cycle of (1) observation, (2) reflection, (3) action planning, (4) to program or action implementation. The results of this KKNT activity are the implementation of various types of activities that are in accordance with the needs of the community, such as Socialization in Elementary Schools, Socialization of UMKM Development, Socialization of Posyandu, and Development of Superior Village Products (Branding Tikar Purun).